Concurrent event‐triggered adaptive neural control for MASS under cross‐water scenarios - Ye, Xiang; Chen, Chao; Zhu, Guibing; Hu, Xin (International journal of robust and nonlinear control, 2024)
This article discusses the control problem of marine autonomous surface ships (MASS) under cross‐water scenarios, that is, from open water to restricted water, where several practical facts, such as uncertain dynamic, unknown disturbance and actuator wear suppression, are taken into account. To resolve such a control design challenge, the predefined performance control (PPC)‐based and barrier Lyapunov function (BLF)‐based ideas are employed, and a prespecified performance function (PPF) is designed to implement the transformation of cross‐water design. Under the adaptive backstepping design framework, with aid of PPC‐based and BLF‐based design ideas, an adaptive neural control solution is developed for MASS under cross‐water scenarios. Furthermore, to reduce the actuator wear and tear caused by high‐frequency corresponding control commands and hull vibration, a new multichannel concurrent event‐triggered protocol (ETP) is constructed in the controller‐actuator (C‐A) channel. Finally, a concurrent event‐triggered adaptive neural control scheme is proposed for MASS under cross‐water scenarios. The theoretical analysis indicates that all signals in the control system are ultimately bounded, and the Zeno behavior is avoided. The simulation and comparison results verify the effectiveness and superiority of the developed control scheme.